DETERMINANTS OF HOUSEHOLD’S POVERTY AMONG CROP FARMERS IN KADUNA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
This study examined the households’ poverty status among crop farmers in Kaduna State. Multi-stage sampling procedure was used to select 242 farmers for this study. Data were collected through using structured questionnaire with the help of trained enumerators. Descriptive and inferential statistics such as tobit regression and Foster, Greer and Thorbecke (FGT) model was employed in this study. The results showed that the mean age of the respondents was 45 years and were married, mean household size of the farmers was 11 persons, and about (80.6%) had formal education. The poverty situation of the farmers revealed that 51% were poor and the strategies adopted by the farmers to combat poverty were mostly through diversification into commercial farming, increased personal savings and involvement in non-farming activities. Tobit regression analysis revealed that age, household and income negatively influences the poverty status of the farmers, statistically significant at 1%, this implied that, poverty is concentrated among households in the study area. Major constraints encountered by the crop farmers, include high cost of inputs, inadequate credit facilities and inadequate market linkages. In conclusion, poverty incidence had a negative and significant effect on rural crop farmers. It was recommended that farmers should form cooperative societies to access micro loan; farmer should be linked to the urban market through extension agent and media to attract good value for their crops. Government and Non-Governmental Organizations (NGOs) should make farm inputs readily available at a subsidized rate
Keywords: Determinants, Households’ poverty, Crop farmers and Kaduna State